Entrepreneurial growth in British regions 1980-1998 - Andre van Stel; David Storey (European Regional Science Association (ERSA), 2002)
This paper examines the relationship between new firm startups and employment growth in Great Britain. We construct a new data set for 60 British regions, covering the whole of Great Britain, between 1980 and 1998. The central theme of the paper is that, with the exception of a recent paper by Audretsch and Fritsch (2002) for Germany, no data set has been available to examine long-run, as well as short-run relationships. The current paper uses a long-run data set and obtains results for Great Britain which are in some respects similar to those for Germany. There are a number of theoretical reasons to expect a positive relationship between the extent to which a geographical area is 'entrepreneurial' and the extent to which it is 'economically successful' (measured as, for instance, the number of jobs created). The first is that if 'entrepreneurial' is reflected in 'new firm formation' then these new firms create jobs directly and so add to the stock of jobs. The second is that the new firms constitute a (real or imagined) competitive threat to existing firms, encouraging the latter to perform better. Finally, new firms provide a vehicle for the introduction of new ideas and innovation to an economy, which has been shown to be a key source of long-term economic growth [Romer 1986]. However, there are also reasons for not expecting firm formation rates to be related to job creation. We mention two of them. The first is that new firms directly contribute only a small proportion of the stock of jobs in the economy [Storey 1994]. Secondly, most new firms are merely displacing existing firms without any observable gain either to the customer or to the economy [Storey and Strange 1991]. To establish the relation empirically, we estimate a model where employment growth is explained by startup activity and some controls, using our long-run data set. Within the period 1980-1998 we analyze different subperiods to examine whether the impact of new firm startups on growth has changed during the last two decades of the 20th century. We explicitly take account of numerous empirical pitfalls. We find evidence for positive employment effects of startup activity for British regions. Two important conclusions can be drawn from our regression exercises. First, the positive impact of new firm startups on employment growth is stronger for the 1990s than for the 1980s. This finding is consistent with Audretsch and Fritsch (2002), who find an increased impact of new firm startups on employment growth for German regions over the last two decades of the 20th century. Second, lag structures are important, and longer lagged startups are found to have a bigger impact on employment growth than shorter lagged startups. This finding is consistent with Audretsch, Carree and Thurik (2001). They investigate the relation between entrepreneurship and unemployment for 23 OECD countries and find empirical evidence for their claim that "the employment impact of entrepreneurship is not instantaneous but rather requires a number of years for the firm to grow". Selected references: Audretsch, D.B., M.A. Carree and A.R. Thurik (2001), "Does entrepreneurship reduce unemployment?", Discussion paper TI01-074/3, Tinbergen Institute, Erasmus University Rotterdam. Audretsch, D.B., and M. Fritsch (2002), "Growth regimes over Time and Space", Regional Studies (forth-coming). Romer, P.M. (1986), "Increasing returns and Long Run Growth", Journal of Political Economy 94, 1002-1037. Storey, D.J. and A. Strange, (1992), "Entrepreneurship in Cleveland 1979-1989: A Study of the Effects of the Enterprise Culture", Employment Department, Research Series No. 3. Storey, D.J. (1994), "Understanding the Small Business Sector", Routledge, London.
Keywords: 330